Physico-chemical properties of spring water near Nowe Miasto nad Pilicą - Łaszewski, Maksym; Stępniewski, Krzysztof; Kowalczyk, Patrycja; Malinowska, Wiktoria; Skorupa, Weronika; Sobkowicz, Aleksandra; Żaba, Klaudia (Acta Geographica Lodziensia, 2024)
The aim of the study was to conduct a preliminary hydrological and hydrochemical investigation of spring waters near Nowe Miasto nad Pilicą. The monitoring covered nine descending springs located within the Pilica erosion scarp on the section from Łęgonice to Wola Pobiedzińska, where water flows out of Quaternary porous formations. Once a month, from November 2022 to October 2023, the discharge, temperature, conductivity, pH and nitrate concentrations were measured, while the chemical composition in terms of macroelements was determined in February and August. Additionally, the concentrations of selected microelements were measured in August. The obtained results indicated that the discharge of the identified outflows placed them in classes VI and VII according to Meinzer classification and was relatively stable over time. In terms of water mineralisation, the springs can be classified as freshwater and acratopegic, with the hydrochemical types being HCO3–Ca and HCO3–SO4–Ca. Significant differences in the physical characteristics and chemical composition of the spring waters were documented (visible in the concentrations of SO42-, Cl-, Na+ and K+), resulting from human impact and good isolation of water-bearing horizons. It was also found that the spring waters were heavily contaminated with nitrates, which reflects the intensive agricultural activity in the Rawska Upland.